Dosimetric evaluation of electron beam Monte Carlo isodoses distribution based on thermoluminescent dosimetry - Flavia dos Reis Gonçalves; Elizabeth Vianello; Claudio Viegas; Alfredo Viamonte (Brazilian Journal of Radiation Sciences)
Electron beams are applied in radiotherapy treatments where superficialized doses are desirable as well as deeper tissues sparing. Monte Carlo method has been recently implemented in the TPS as the algorithm for electron beam isodoses calculation at the National Institute of Cancer in Brazil. This work comprises an additional method of evaluation of the isodoses generated by the TPS, considering the irradiation of a non-flat surface. A 6-Gy electron beam breast irradiation was planned and delivered to an anthropomorphic phantom into which 36 capsules with TLD100 were inserted. The TLD calibration curve was performed from 100 cGy to 700 cGy. In an overall analysis, eMC algorithm isodose distribution results agreed with TLD measured doses. 75% of measured data met the 5% accuracy criteria, which can be considered in good agreement with the recommended uncertainties involved in a radiotherapy treatment. Considered all collected data, 8 TLDs received extremely low doses and due to tissue attenuation of the electron beam, the TLD measurements might have additional uncertainties. If these data are not taken into account, 100% of the measured doses, considering the uncertainties, meet the 5% accuracy criteria. About the 3 methods for isodose smoothing available in the eMC algorithm, the low level of dose smoothing option provides the best matching with measured data, consisting of the most reliable option. Considering the AAPM recommendations eMC algorithm offers an accurate solution for isodoses calculation, within a 5% accuracy.